Short-term Results of the Treatment of Hip Fractures in Children - Hodgson Ovalle, Felipe; Moller, Francesca; Angulo, Manuela; Figueroa, Maria-Jesus; Gündel, Alejandro; Cañete, Ismael (Revista Chilena de Ortopedia y Traumatología, 2022)
Introduction Pediatric hip fractures are infrequent, associated with high-energy trauma, and present devastating complications. Most cases are treated surgically using different types of fixation. The objective of the present study is to report the results of a series of cases of surgical patients in two reference hospitals in Chile.Materials and Methods A case series which included pediatric patients diagnosed with hip fractures and treated surgically between 2004 and 2008. We performed descriptive statistics for the demographic variables, the energy of the accident, the Delbet classification, the type of treatment, the osteosynthesis technique, of complications, and the clinico-radiological evaluation according to evaluation.Results A total of 17 cases were evaluated, 76.5% of which were secondary to high-energy accidents. The median age of the sample was of 7 years, and it was composed of 58.8% of girls. There were 3 cases of Delbet type II, 9 of type III, and 5 of type IV. As fixation method, we used cannulated screws (9 cases), locking compression plates (LCPs; 5 cases), dynamic hip screws (DHSs; 2 cases), and dynamic compression plates (DCPs; 1 case). The median follow-up was of 2.3 years (range: 0.5 to 12.8 years). Complications were observed: coxa vara in one case, and discrepancy in the length of the lower extremities in another case, and there were no cases of osteonecrosis. Osteosynthesis removal was performed in seven patients. Good results were obtained in all patients according to Ratliff criteria.Conclusions Most fractures were associated with high energy trauma, with the most frequent being type III on the Delbet classification. All the patients were treated surgically, with good results, with no cases of osteonecrosis.Level of evidence: 4.
Keywords: hip fractures; osteosynthesis; children